The Effect Of The Use Of Crossword Puzzle Media On Students' Vocabulary Mastery - Safitri, Safitri; Suryadi, Suryadi (Journal of Educational Sciences, 2023)
The kids' vocabulary prevented them from fully mastering the four pillars of English language proficiency. As a result, it was decided to investigate "The Effect of Crossword Media on Students' Vocabulary Acquisition and Oral Communication." To improve their English, students can look into ways to expand their vocabulary and practice public speaking. After giving some thought to a number of potential approaches to the classroom, the author settled on using crossword puzzles as a means of fostering student growth in these areas. The objectives of this study were to: (1) give a general overview of how crossword puzzles can aid in vocabulary development and retention; (2) offer suggestions for future research; and (3) describe how crossword puzzle-containing media influences students' capacity to learn new words. After information was gathered via a questionnaire, quantitative data analysis was done. A representative sample of SMPIT Bait Et-Tauhied students participated in the study. We sent a questionnaire with 20 distinct sets of statements to 30 students in order to conduct the study. The results demonstrate that a crossword puzzle significantly affects students' understanding and use of va because the validity test of the test with the calculated R value is greater than the R table, demonstrating the validity of the 20 questions completed by the respondents. Additionally, the reliability test using Croanbach alpha demonstrates very reliability, and the case processing summary demonstrates that the number of respondents when filling out the questionnaire is not lost or broken.